IQ - Ide, Joe (New York : Mulholland Books/Little, Brown and Company, 2016)
A resident of one of LA's toughest neighborhoods uses his intellect to solve the crimes the LAPD doesn't have time to pursue. He's a loner and a high school dropout, his unassuming nature disguises a relentless determination and a fierce intelligence. He charges clients whatever they can afford, which might be a set of tires or a homemade casserole. To get by, he's forced to take on clients that can pay.
Keywords: Private investigators -- Fiction; Los Angeles (Calif.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)